2020
DOI: 10.3390/ijerph17155511
|View full text |Cite
|
Sign up to set email alerts
|

Between Migrant Care Work and New Occupational Welfare Tools: Changing Home Care Arrangements in Italy

Abstract: Austerity measures on services provision, introduced due to recent economic crises, have stimulated the search for innovative welfare solutions, including options that are not directly or entirely funded by public sources. In Italy, recent legislation has promoted the development of occupational welfare (OW) measures, aimed at strengthening the supply of services to support employees with informal (elder) care responsibilities. This paper aims to describe how the newly introduced OW schemes might innovate exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Starting from these considerations, it seems necessary to integrate PCAs in the Italian LTC system, also impacting its sustainability [ 73 , 88 ], within the network of local services, and to provide incentive systems, as follows: fiscal benefits for related expenses [ 89 ]; means-based assessment of the IA to identify people most in need of financial assistance [ 57 , 61 ]; and care allowances for regular hiring of PCAs [ 90 ]. Irregular employment impacts indeed their working conditions [ 81 ], which in turn impact quality standards of care services for older people [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starting from these considerations, it seems necessary to integrate PCAs in the Italian LTC system, also impacting its sustainability [ 73 , 88 ], within the network of local services, and to provide incentive systems, as follows: fiscal benefits for related expenses [ 89 ]; means-based assessment of the IA to identify people most in need of financial assistance [ 57 , 61 ]; and care allowances for regular hiring of PCAs [ 90 ]. Irregular employment impacts indeed their working conditions [ 81 ], which in turn impact quality standards of care services for older people [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies(16) were literature reviews (7,12,17,18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) that three of them had scoping (18), systematic (7) and integrative (29) design and used peer review studies to explain home care in the target countries. Seven studies (10,(33)(34)(35)(36)(37)(38) were also document reviews, which means that they gathered information and data from reputable organizations such as World Health Organization, the Insurance Organization or the Ministry of Health and such organizations.…”
Section: Design Of Studiesmentioning
confidence: 99%
“…Although marketization increases QoC, but some challenge comes with the emergence of the gray market, where families employ immigrants without valid certi cates for care in order to reduce costs (21, 35, 39)(6) (25,34). High-income are likely to pay higher co-payments or out-of-pocket to use private caregivers to meet their needs.…”
Section: • Third Domain: Bene Tsmentioning
confidence: 99%
“…Research has commonly identified love and affection as the primary motivation for adopting a typically unpaid caregiver role [ 7 , 8 ] along with motives of duty and reciprocity [ 9 ]. However the complexity of dyadic relationships and attachments [ 10 , 11 , 12 , 13 , 14 ], the existence of varying cultural norms, values and obligations [ 15 , 16 ], competing social and economic demands on potential caregivers [ 17 ] and the fact that modern families tend not to be as geographically co-located as in previous generations [ 18 , 19 , 20 , 21 , 22 ] are less typically examined in relation to their influence on caregiver motivations. We face major challenges if we are to meet the demand for care (including informal care) across Europe on a societal (and often familial) assumption of family member willingness to adopt a caregiving role in the home or community.…”
Section: Introductionmentioning
confidence: 99%